The profitability analysis of factoring companies in Malaysia / Mohd Ridhuan Harun - Harun, Mohd Ridhuan (1994)
This research analyzes the impact of the chosen factors namely Gross Domestic Product, Manufacturing Index and Demand for Account Receivables on the profitability of factoring companies and to determine the factors that most effect the profitability of factoring companies. Companies that are selected for this study are those which offer only factoring facilities and exclude those which provide other financing facilities besides factoring. A total of seven factoring companies which have been in operation for the past seven years were selected. This study will cover the periods from 1987 to 1993. The results of the study indicate that Gross Domestic Product plays the vital role in determining the performance and profitability of the factoring companies. The results of this study was obtained by using various statistical analysis.